(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Clavicle fusion surgery with screws is a popular surgery and is implemented in most orthopedic departments. To evaluate, analyze, learn from, and select effective treatment methods, we conducted this study. Objectives: Description of early results of surgical treatment of bone fusion with screws in patients with closed middle 1/3 clavicle fractures at Can Tho Central General Hospital in 2023. Research method: Retrospective description of 59 patients with closed middle 1/3 clavicle fractures undergoing bone fusion surgery with screws at Can Tho Central General Hospital from January 1, 2023 to December 31, 2023. Results: The group of patients with clavicle fractures is mainly men (81.4%), in the working age group 30 - 60 years old (69.5%), working as farmers/workers and the cause is common. The most common is traffic accidents (84.7%). The mechanism of injury is 69.5% of falls on hands and 30.5% of falls on shoulders. 98.3% had symptoms of swelling and pain, 39% of cases had bulging bones under the skin, 32.2% had shortened shoulders, 11.9% had drooping arms, and 10% had sharp pain and bone crunching. The majority of cases of clavicle fractures that were fused with a screw brace showed no displacement on X-ray (91.5%) and healed in the first stage of surgery (96.5%), with only a small percentage occurring. Complications such as slight displacement or superficial surgical wound infection. The rate of patients achieving good results is 91.5% and quite good is 8.5%. Conclusion: Clavicle fusion surgery with screws is quite good clinically and radiologically, with high success rate, short hospital stay and few complications. This is an effective treatment option for clavicle fractures.